p62 mRNA suppresses NLRP1 expression in cutaneous SCC cells through miR-34a-5p - Paulina Hennig; Patrick Turko; Michela Di Filippo; Mitchell P. Levesque; Thomas Kündig; Hans-Dietmar Beer (Cell Death and Disease)
Abstract The inflammasome sensor NLRP1 is mainly expressed by epithelial cells including keratinocytes of human skin. Germline gain-of-function mutations in NLRP1 cause inflammatory skin syndromes and predispose patients to the development of cutaneous squamous cell carcinomas (cSCCs), a major type of skin cancer originating from keratinocytes. However, expression of NLRP1 is strongly reduced in cSCCs suggesting a complex role of the NLRP1 inflammasome in the development of this type of skin cancer. Suppression of NLRP1 expression in SCC cells is partially caused by an increase in p62 (SQSTM1), a cargo receptor for autophagy-dependent protein degradation. p62 is upregulated in numerous types of cancer and plays key roles in tumor development by activating different pathways. Here, we characterized the molecular mechanisms underlying suppression of NLRP1 expression by p62 in cSCCs. In SCC cells, NLRP1 activation is rescued by a knockdown or knockout of p62 mRNA and, consequently, protein expression, rather than by a knockout of p62 protein expression only. As these experiments suggest a regulation of NLRP1 by the p62 mRNA, we characterized p62 mRNA-regulated gene expression in SCC cells through RNA sequencing. In addition to mRNAs, we identified several differentially regulated microRNAs (miRs), including miR-34a-5p. These short non-coding RNAs regulate the stability or translation of mRNAs in a dynamic manner and a single miR can target multiple mRNAs. miR-34a-5p is an established tumor suppressor in different types of cancer and its expression is also downregulated in cSCCs. Although miR-34a-5p seems to bind neither p62 nor NLRP1 mRNA directly, it increases NLRP1 expression, most likely through an indirect and complex mechanism, which occurs at the RNA level. In summary, our findings revealed a novel pathway regulating suppression of the inflammasome sensor NLRP1 in SCC cells by p62, which occurs at the mRNA level and is mediated by miRs, including the tumor suppressive miR-34a-5p. Therefore, a pharmacological increase in miR-34a expression represents a treatment option for cSCC patients that allows not only to target know proteins regulated by miR-34a but also a reconstitution of NLRP1 expression.